The Measurement of Real Expenditure on R&D for Ukraine - Zhukovich, Inna; Ryzhkova, Julia (Lithuanian Journal of Statistics, 2012)
The measurement of real research and development (R&D) expenditures is an issue for discussion, especially forcountries with a high inflation, when general price indices do not correctly reflect trends in the cost of performing R&D. Theaim of this paper is to present the procedure for the calculation of R&D price indices for Ukraine, which takes into accountspecific features of the country’s research system. The paper analyses the theoretical background of the measurement of realR&D expenditures and methodological approaches to the calculation of R&D price indices. We have applied a FrascatiManual recommendation, according to which components of R&D expenditure are deflated by specific price indices. Theexperimental calculations of real R&D expenditures for Ukraine for the period 2001-2010 and the construction of R&D priceindices are presented in this paper. The results obtained are new for Ukrainian statistics and they will be used in R&Dstatistics practice in Ukraine.
Keywords: research and development (R&D); R&D expenditures; R&D price index; R&D components; R&D deflator